Should egalitarians expropriate philanthropists? - Indraneel Dasgupta; Ravi Kanbur (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
Wealthy individuals often voluntarily provide public goods that the poor also consume. Such philanthropy is perceived as legitimizing one's wealth. Governments routinely exempt the rich from taxation on grounds of their charitable expenditure. We examine the normative logic of this exemption. We show that, rather than reducing it, philanthropy may aggravate absolute inequality in welfare achievement, while leaving the change in relative inequality ambiguous. Additionally, philanthropic preferences may increase the effectiveness of policies to redistribute income, instead of weakening them. Consequently, the general normative case for exempting the wealthy from expropriation, on grounds of their public goods contributions, appears dubious.
Keywords: D31; D63; D74; Z13; 330; Community; Public goods; Inequality; Distribution; Philanthropy; Egalitarianism; Vermögen; Öffentliches Gut; Wohltätigkeit; Steuerbegünstigung; Einkommensverteilung; Wirtschaftsmodell